THE PROCESS OF PUBLIC SERVICE MODERNIZATION - Дибань, Максим Петрович; Ніколаєнко, Інна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
The purpose of this article is to analyze the process of public service modernization and to focus on the processes of improving the current law of 2016 related with issue of reducing the impact of the Labor Code on the normative legal documents that are concerned with public service. The methodological basis of the research comprises general scientific and special methods: formal-logical, functional-legal and system-structural methods. Results: the term «modernization» of public service is complementary to provisions of current law, especially, in the transparency of staff selection process for public service. Discussion: possibilities of applying different approaches of scientists to changes in the Law of Ukraine «On Public Service». All aspects of the public service, features of the competition for job vacancies, requirements for candidates and the main innovations in this field are analyzed. The conducted research made it possible to conclude that the institutional changes according to the system of «modernization» of the authorities should be: a) reorganization of ministries; b) establishment of public service performance criteria; c) dismissal of unscrupulous and corrupt executives; d) establishment of the vertical system of responsibility: government order – ministry assignment – department assignment – execution by emloyee. The significant disadvantage of using the provisions is that what is being reviewed does not become an effective tool for simply being dishonest. In the previous version of the law, there were a number of negative factors for the broad retention of duties. An inefficient institution is the one that implements only 20 percent of government contracts, and where the executives receiving 200 percent of the rewards. Public service must involve conscientious and responsible employees, so it should be an open and transparent system in this regard.